To a question of self-taxation of citizens - B. R. Krasnicky (Путеводитель предпринимателя, 2020)
To a question of self-taxation of citizens The article examines the nature of the phenomenon of «self-taxation of citizens», as well as questions of its practical application. There are proposed the directions of development of this system, what will help meet the diverse needs of local communities.